Major Polymorphisms of Genes Involved in Homocysteine Metabolism in Malaria Patients in Ouagadougou, Burkina Faso. (18th May 2017) - Yameogo, Noé; Bazie, Bapio Valérie Elvira Jean Télesphore; Ouattara, Abdoul Karim; Yameogo, Pouiré; Compaore, Tegwinde Rebeca; Obiri-Yeboah, Dorcas; Djigma, Florencia Wenkuuni; Karou, Simplice Damintoti; Simpore, Jacques
Abstract : This study analyzed the four main polymorphisms of the genes in homocysteine metabolism in malaria patients. Forty-two randomly selected subjects, diagnosed positive for Plasmodium falciparum, were included. The four genotypes were detected by real-time PCR using the MTHFR 677C>T, MTHFR 1298A>C, MTR 2756A>G, and MTRR 66A>G detection kit (Sacace Biotechnologies REF: T01002-96-S). The results revealed frequencies of 90% 677CC, 10% 677CT, and 00% 677TT for MTHFR C677T; 78.6% 1298AA, 19% 1298AC, and 2.4% 1298CC for MTHFR A1298C; 61.9% 2756AA, 33.3% 2756AG, and 4.8% 2756GG for MTR A2756G; and 50% of 66AA, 45% of 66AG, and 5% of 66GG for MTRR A66G. Correlations were found between A2756G MTR genotypes and parasitaemia (P = 0.02 ), MTRR A66G and hemoglobin genotypes (P = 0.009 ), and MTHFR A1298C and sex (P = 0.01 ). This study demonstrated for the first time an association between the A2756G MTR alleles and Plasmodium falciparum malaria in Burkina Faso and gave an overview of the genotypic distribution of the major SNPs influencing the metabolism of homocysteine.